Adolescents Cyberbullying: Examining The Role of Social Media Use Intensity and Dark Triad Personality - Adinata, Surya Prawira; Kesumaningsari, Ni Putu Adelia; Setiasih, Setiasih (Universitas Ahmad Dahlan, 2024)
Cyberbullying is a form of harassment carried out through electronic devices, often involving social media platforms. This study aimed to determine the role of social media use and dark triad personality in predicting adolescents’ involvement in cyberbullying. The study involved 219 adolescents aged 12-21 who had engaged in cyberbullying within the past six months. Data were collected using three scales: the Social Media Use Integration Scale, Short Dark Triad, and Cyber-Aggression Scale. The results indicated that both intensity of social media use and dark triad personality traits simultaneously predicted cyberbullying behavior among adolescents, with psychopathy emerging as the most significant contributor to the observed behaviors. The study suggests that while social media use alone may not directly lead to cyberbullying, it serves as a facilitating platform for individuals with psychopathic tendencies. The study’s findings highlight the importance of parents, counselors, and the community working together to prevent cyberbullying behaviors among adolescents.